MANAJEMEN BIMBINGAN DAN KONSELING DI MAN 1 MEDAN - Amelia, Dina Nadira (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
This study aims to find out in depth about the implementation of guidance and counseling management in MAN 1 Medan. This study intends to examine the behavior of madrasah principals, coordinators of guidance and counseling and counselors or guidance and counseling teachers in planning, organizing resources, implementing plans, and evaluating guidance and counseling activities in MAN 1 Medan. This study used qualitative research methods. The research instrument is the researcher himself, using data collection tools consisting of observation, interviews, and document studies, while the validity and reliability of the data uses triangulation between methods and between informants, which consists of the head of the Madrasah, the Coordination of Guidance and Counseling, counseling teachers or counselors. . The data analysis techniques for the interactive model of Miles and Huberman are; data reduction, data exposure, and drawing conclusions about management guidance and counseling. There are three findings in this study, namely: (1) The process of planning guidance and counseling at MAN I Medan is carried out through deliberations involving the head of the madrasah, deputy head of Madrasah, homeroom teacher, BK coordinator, TU, and BK teachers, therefore BK planning here a systematic collaborative model, (2) The implementation of the guidance and counseling plan refers to the characteristics of individual guidance and career guidance activities. Individual BK activities towards students of MAN 1 Medan, especially those who want to continue their education to higher education and reduce delays in students entering school, (3) Evaluation of guidance and counseling activities at MAN 1 Medan is carried out through the making of BK field reports to the school principal, and enforced supervision by the head of madrasah on various guidance and counseling activities carried out by BK teachers.